Adsorption characteristics of lead from aqueous solution by pyrolysed used bleaching clay - Norazura, Abd Jalil (2009)
This study was conducted to investigate the adsorption characteristics of lead (Pb) from aqueous solution by pyrolysed used bleaching clay. Used bleaching clay, a waste from an edible oil refinery has been treated by pyrolysis in a furnace. The used bleaching clay was pyrolysed at four temperatures which is 500°C, 600°C, 700°C and 800°C. The pyrolysed samples were characterized using Thermogravimetric Analysis (TGA) to find the carbon content. The parameter involves in this experiment are contact time, pH of solution, initial concentration and carbonization temperature. The Langmuir sorption isotherm was plotted to describe the equilibrium adsorption and the maximum sorption capacities of the bleaching clay towards Pb. From the adsorption kinetics experiment, it was clearly observed that the concentration of Pb decrease as time increased until it reaches the equilibrium time while the uptake capacity increase as time and initial concentration increased. For the effect of pH of adsorption solution, the highest maximum sorption capacity was determined at pH 6 and the carbonization temperature that yields highest sorption capacity is 600°C. This experiment was repeated for another adsorbent which is the untreated clay and the natural bleaching clay for comparison.